Kinematics and electromyographic activity of horse riders during various cross-country jumps in equestrian - Guillaume, J. F.; Laroche, D.; Babault, N. (Sports Biomechanics, 2021)
The objective of this study was to identify the key biomechanical patterns (functional muscles and kinematics) of amateur horse riders during various cross-country jumps in equestrian. Eleven riders first performed a control condition that corresponded to jumps over three different obstacles (log wall, brush and tree trunk) before jumping over the same three obstacles in a cross-country course. 3D Kinematics and electromyographic (EMG) activity was synchronously collected which included seven muscles of the riders back, lower and upper limbs. Maximum voluntary isometric strength of knee extensors was also measured before and immediately after the race to investigate potential fatigue. Our results showed similar EMG activity for the different obstacles. Whereas some kinematics alterations were observed between obstacles. Moreover, back movements alterations were recorded between the jumps of the cross-country as compared to the control condition. Finally, muscle strength was not altered after the race. In conclusion, our study indicates that upper and lower body muscles contributed to the realisation of various jumps during a cross-country and that the different configurations of the obstacles did not induced specific muscular and kinematic responses.